2022
DOI: 10.1097/rhu.0000000000001818
|View full text |Cite
|
Sign up to set email alerts
|

Proportionate Cardiovascular Mortality in Chronic Inflammatory Disease in Adults in the United States From 1999 to 2019

Abstract: Background: Despite a rising prevalence of chronic inflammatory disease (CID), the recent trends in cardiovascular disease (CVD) mortality of patients with CID is scarce. In this study, we investigated patterns of CVD mortality in systemic lupus erythematosus (SLE), inflammatory bowel disease (IBD), and rheumatoid arthritis (RA) compared with the general population.Methods: We used the 1999 to 2019 multiple causes of death files from the national center for health statistics to analyze patterns and trends of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…RA-related extra-articular manifestations and comorbidities are associated with exacerbated outcomes of the patients. Studies have demonstrated that respiratory diseases, cardiovascular diseases and neoplasms are the primary causes of death in RA patients [ 32 34 ]. The 1-year, 5-year and 10-year mortality of RA-associated ILD was 13.9%, 39.0% and 60.1% in a population-based cohort study [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…RA-related extra-articular manifestations and comorbidities are associated with exacerbated outcomes of the patients. Studies have demonstrated that respiratory diseases, cardiovascular diseases and neoplasms are the primary causes of death in RA patients [ 32 34 ]. The 1-year, 5-year and 10-year mortality of RA-associated ILD was 13.9%, 39.0% and 60.1% in a population-based cohort study [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, dysregulations in the intestinal microbiome and immune system also affect other organs, such as the brain, promoting the development of neurodegenerative disorders ( 6 ). Moreover, there is currently no cure for chronic diseases, although medical advances in disease management significantly decreased mortality in the past decade ( 7 ). Still, 3 out of 5 people die due to chronic inflammatory diseases worldwide ( 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…Herein, we sought to identify the pattern of PVD mortality that has evolved over the past 2 decades. For this, we used the Centers for Disease Control and Prevention’s Wide‐Ranging Online Data for Epidemiologic Research database 10 , 11 to identify the change in PVD mortality from 1999 to 2019 by racial background.…”
mentioning
confidence: 99%